1994
DOI: 10.1007/bf01753839
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic potential of human colorectal carcinoma SW1222 cells transfected with cDNA encoding carcinoembryonic antigen

Abstract: In order to examine a role of carcinoembryonic antigen (CEA) in metastasis, cDNA encoding CEA was introduced into a clone of human colorectal carcinoma SW1222 cells. Western blot analysis revealed that all transfectants express CEA of 180 kDa while the parent clone does not. In the transfectants, the level of CEA expression in clone 3 was higher than that of clone 1. Clone 3 formed aggregates rapidly after suspended by trypsinization while clone 1 did not. In experimental metastasis assay where tumor cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…It is expressed in a number of tumors of epithelial origin, including colorectal carcinoma, lung adenocarcinoma, and mucinous ovarian carcinoma (30). CEA has been reported to promote the metastatic potential of colon cancer cells (31,32). The capacity of different colorectal cell lines to grow in nude mouse spleen and liver models correlates positively with CEA production (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in a number of tumors of epithelial origin, including colorectal carcinoma, lung adenocarcinoma, and mucinous ovarian carcinoma (30). CEA has been reported to promote the metastatic potential of colon cancer cells (31,32). The capacity of different colorectal cell lines to grow in nude mouse spleen and liver models correlates positively with CEA production (33).…”
Section: Discussionmentioning
confidence: 99%
“…B In PCa, CEACAM5 expression patterns were well correlated with tumor Gleason grading, and there was significant difference in expression patterns (p=0.010). According to the histological grading, poorly differentiated carcinomas showed more cytoplasmic staining [8], while the well differentiated displayed more membranous CEACAM5 staining (Figure 2A, B, C). The 9 cases with membranous staining have lower Gleason grading while the 24 cases with cytoplasmic staining have higher Gleason grading on average.…”
Section: Detection Of Ceacam5 Expressionmentioning
confidence: 99%
“…Indeed, the tumorigenic functions of CEACAM5 have been demonstrated in both 3D culture of colon carcinoma cell lines in vitro [4] and CEABAC transgenic mice in vivo [5,6]. However, a number of studies have indicated that CEACAM5 contributes to the tumor invasion and metastasis in human colorectal carcinoma [7,8]. Most of the current studies on CEACAM5 focus on gastrointestinal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…They found that among the 171 unique proteins identified in these exosomes, many were associated with cancer cell proliferation, invasion, and metastasis such as c-Met protein (hepatocyte growth factor receptor), amphiregulin (AREG), various ephrins (EFNB1, EFNB2), and Eph receptors (EPHA2-8, EPHB1-4), components involved in Wnt (␤-Catenin and TNIK) and Ras (CRK and GRB2) signaling, and several key components associated with colorectal cancer, including CEACAM1 and 5, FAT1, and CDH17 [74]. It is a well-known fact that CEACAM5 (CEA) is found to be overexpressed in over 90% of human gastrointestinal and pancreatic cancers and, in particular it is associated with metastatic potential in colon cancer [78,79] (Table 1).…”
Section: Proteomics Data Set Of Tdesmentioning
confidence: 99%